2020
DOI: 10.1139/cjm-2020-0244
|View full text |Cite
|
Sign up to set email alerts
|

Uneven genotypic diversity of Escherichia coli in fecal sources limits the performance of a library-dependent method of microbial source tracking on the southwestern French Atlantic coast

Abstract: To develop a library-dependent method of fecal sources tracking, a reference library of 6,368 Escherichia coli isolates was constructed based on fecal samples collected around the Arcachon Bay, in 2010, and in French Basque Country, Landes and Béarn, between 2017 and 2018. Different schemes of source identification were tested: use of the complete or filtered library; characterization of the isolates based on ERIC – PCR or MALDI-TOF mass spectrometry; assignment using either similarity-based classifiers or SVM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Lyautey et al (2010) reported an accuracy of 77% using BOX and ERIC libraries, while Mohapatra et al (2007) achieved 79.89% in GTG(5) library. Other gel fingerprinting studies have used different classifiers such as discriminant analysis (Dombek et al 2000;Mohapatra et al 2007;Somarelli et al 2007), support vector machines (Garabetian et al 2020), kNN and neural networks (Carlos et al 2012) with lower or similar accuracy rates. Robinson et al (2007) suggested kNN as a compromise between the strengths of maximum similarity (MS) and discriminant analysis in terms of accuracy and prediction bias when dealing with disproportionate libraries.…”
Section: Mst Fingerprint Librarymentioning
confidence: 99%
“…Lyautey et al (2010) reported an accuracy of 77% using BOX and ERIC libraries, while Mohapatra et al (2007) achieved 79.89% in GTG(5) library. Other gel fingerprinting studies have used different classifiers such as discriminant analysis (Dombek et al 2000;Mohapatra et al 2007;Somarelli et al 2007), support vector machines (Garabetian et al 2020), kNN and neural networks (Carlos et al 2012) with lower or similar accuracy rates. Robinson et al (2007) suggested kNN as a compromise between the strengths of maximum similarity (MS) and discriminant analysis in terms of accuracy and prediction bias when dealing with disproportionate libraries.…”
Section: Mst Fingerprint Librarymentioning
confidence: 99%
“…For instance, Dela Peña et al [24] established a fecal source library with rep-PCR fingerprints of a variety of hosts to study fecal contamination sources in Laguna Lake (Philippines). Similarly, an E. coli-based fecal library was created for source tracking on the French Atlantic coast [25]. However, the authors indicated that the uneven genotypic composition of the library with a high proportion of nondiscriminatory genotypes hampered its performance in MST analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The inventory of host-specific/associated genetic markers is constantly expanded and is increasingly exploited for qualitative and quantitative MST analyses in different water environments across the world [3,5,9,14,21,[23][24][25][26][27][28]. The majority of genetic markers are developed to target the 16S rRNA gene of Bacteroides spp.…”
Section: Introductionmentioning
confidence: 99%